Comparative Analysis Study on Construction Cost Between Concrete Structures and Steel Structures Buildings in Surabaya - Deviany Kartika; Hadi Surya Wibawanto; Tiong Iskandar; Wahyu Bangkit Pangestuaji (Universitas Islam Sultan Agung, 2022)
High-rise buildings in Indonesia must be designed resistance to receiving earthquakes. This is because the earthquake load that occurred in Indonesia has a high intensity. So that existing buildings, especially multi-story buildings must ensure good performance in receiving earthquake loads. This effort aims to maintain the safety of its users. Several aspects that need to be considered in designing earthquake-resistant buildings are structural performance and construction costs. Therefore, in this study, we will discuss the designed of earthquake-resistant structures by making comparisons on concrete structures and also steel structures which will then analyze the cost of the structure for the structures that have been analyzed and designed. From the results of the analysis, for the same conditions, earthquake resisting frame with reinforced concrete construction, it requires cheaper construction costs compared to steel construction. Concrete construction requires a structural cost of Rp. 19,030,188,114.0 and for a steel structure of Rp. 72,206,697,860.7. This is certainly not a conclusion that concrete construction is superior to steel construction. Because even though it is more expensive in terms of cost, steel construction is quite superior in terms of quality, time efficiency and ease of implementation.